Bilimbi Fruit (Averrhoa bilimbi) Juice: Nutritional Analysis and Microbial Analysis - D. Astillo, Jessica (International Journal of Environment, Agriculture and Biotechnology, 2022)
Food’s nutritional analysis guarantees that it contains the correct number of vitamins and minerals while also allowing for a better understanding of the food's fat, carbohydrate dilution, protein, fiber, sugar, etc. Identifying pathogens and food spoilage microorganisms is essential to food microbiology because it ensures consumer safety, prevents brand desecration, and reduces the cost of remediation after failed inspections or food poisoning outbreaks. This study's primary objective was to determine the nutritional content and identify the hazardous microbes in the Bilimbi Fruit (Averrhoa bilimbi) Juice. The study used an experimental methodology and underwent careful analysis to get detailed results regarding the product. To ascertain the product's nutritional value, samples of the three treatments—plain, grapes, and apple—were sent to theF.A.S.T. Laboratory. Analysis revealed that Bilimbi Fruit (Averrhoa bilimbi) Juice contains Vitamins and minerals that benefit consumers; it includes Crude Fiber, Calcium, Vitamin C, and phosphorus. The result is that each of the three treatments' nutritional contents of "Bilimbi Fruit Juice" is within the recommended dietary requirement for Filipinos. Microbial Analysis reveals no hazardous microbes and bacteria found in the products. Therefore, Bilimbi Fruit Juice is an organic and nutritional juice safe for consumption and an excellent alternative to existing fruit juice on the market.